Expression of physiological sensation of anatomical patterns in wood: An event-related brain potential study - Sha Sha Song; Guang Jie Zhao (BioResources, 2012)
The emotional and psychological activities associated with the visual perception of macroscopic and microscopic structure patterns of wood were investigated. The macroscopic and microscopic structure patterns of 18 different timber tree species of northeast China were selected as the research objects, and these were divided into eight categories for event-related potential analysis. The 30 effective subjects’ tasks were to watch the wood structure stimuli patterns and evaluate them on a 7-point bipolar scale. The results showed that the emotional valence of the wood structure stimuli patterns of the eight categories evoked P2 and late positive potential (LPP) composition in a specific area of the brain. P2 refers to an early perception analysis processing for visual perception of the wood stimuli patterns, while LPP refers to late processing and reflects evaluations when people face different wood stimuli patterns. The results also indicated that people prefer to connect the understanding of macroscopic and microscopic patterns of wood with their own mood. Evaluation processing for macroscopic and microscopic structure patterns of wood were based on visual perception analyses, which were judged by personal feelings and decisions. People made active emotional assessments of the macroscopic and microscopic structure patterns of wood.